Quantitative MRI protocol and decision model for a ‘one stop shop’ early-stage Parkinsonism diagnosis: Study design - Samy Abo Seada; Anke W. van der Eerden; Agnita J.W. Boon; Juan A. Hernandez-Tamames (NeuroImage: Clinical, 2023)
Differentiating among early-stage parkinsonisms is a challenge in clinical practice. Quantitative MRI can aid the diagnostic process, but studies with singular MRI techniques have had limited success thus far. Our objective is to develop a multi-modal MRI method for this purpose. In this review we describe existing methods and present a dedicated quantitative MRI protocol, a decision model and a study design to validate our approach ahead of a pilot study. We present example imaging data from patients and a healthy control, which resemble related literature.